Training of Community Cadres in the Rapid Response Team for Dengue Fever Control at Wiyung Health Care Center, Surabaya - Sulistiawati sulistiawati; Lynda Rossyanti; Bilqis Inayatillah; David Nugraha; Muhammad Ilyas Adi N (Journal of Community Medicine and Public Health Research, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Indonesia, particularly in endemic areas. Early prevention and intervention efforts are essential to reduce incidence and transmission. This community service program aimed to enhance community health cadres' knowledge of DHF infection and strengthen the Rapid Response Team's (TGC) role in early detection and rapid response systems. Pre-test results showed that 96.3% of participants understood the basic context of DHF, including transmission and prevention through the 3M Plus mosquito nest eradication program. However, some participants lacked a comprehensive understanding of the TGC concept, including organizational structure, primary duties, and coordination flow with primary health centers or health departments. Following an interactive education and training session, post-test results showed a significant improvement, with 100% of participants demonstrating a sound understanding of the TGC’s role and function. This improvement indicates that participatory educational activities can effectively enhance community health literacy. This community service is expected to be a stepping stone toward developing a swift reporting system, strengthening DHF handling SOP implementation, and increasing community preparedness to face potential outbreaks in their respective areas.